Pengenalan Jenis Platform & Sistem Pengeboran Pada Pembelajaran Praktikum Peralatan Pengeboran Migas - Dellonix Mealea Vecia; Atala Rifqi Fadilah; Debby Nur Fitria; Huldiah; Rachmasari Pramita Wardhani (Kodepena (Komunitas Dosen Penulis dan Peneliti Indonesia), 2025)
As technology advances and energy demand increases, a thorough understanding of the various types of drilling platforms and systems is becoming increasingly important, especially for students pursuing engineering, energy, or environmental sciences. This knowledge will not only aid in understanding complex industrial processes but also prepare them to address the challenges and opportunities present in the oil and gas sector. By understanding various types of drilling platforms and systems, students are expected to be able to explain the characteristics, advantages, and disadvantages of each type, as well as the factors influencing the selection of the appropriate platform and system for specific conditions. This research is expected to be a useful source of information and support the development of student competencies in their fields, enabling them to contribute effectively to the oil and gas industry in the future. Keywords: Introduction, Platform, Drilling System, Practical, Oil and Gas